2014
DOI: 10.1186/1749-8546-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Popularity and customer preferences for over-the-counter Chinese medicines perceived by community pharmacists in Shanghai and Guangzhou: a questionnaire survey study

Abstract: BackgroundThis study interviewed community pharmacists in Shanghai and Guangzhou for their perception of the popular categories of over-the-counter (OTC) Chinese medicines and the factors affecting customer preferences for OTC Chinese medicines.MethodsA cross-sectional survey was carried out in six main administrative districts in Guangzhou and eight main administrative districts in Shanghai, China. Descriptive statistical analysis was conducted in this study.ResultsOTC Chinese medicines contributed 21–50% amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Majority of our study subjects (28.8%) selected the antibiotics on recommendation from dispensing counter, and 21.2% from past experiences and left-over strips. This observation correlates with two recent studies [9][10][11][12][13][14][15][16] where 67.3% subjects procured their medicines from retail medicine shops and the rest from left over medicines. Another study from outside India 7 reported ADRs with self-medication in 16.7% of the respondents, while in our study 13.3% of the subjects reported the ADRs.…”
Section: Discussionsupporting
confidence: 77%
“…Majority of our study subjects (28.8%) selected the antibiotics on recommendation from dispensing counter, and 21.2% from past experiences and left-over strips. This observation correlates with two recent studies [9][10][11][12][13][14][15][16] where 67.3% subjects procured their medicines from retail medicine shops and the rest from left over medicines. Another study from outside India 7 reported ADRs with self-medication in 16.7% of the respondents, while in our study 13.3% of the subjects reported the ADRs.…”
Section: Discussionsupporting
confidence: 77%
“…The other incompatible result was shown by Emmanuel et al (2014) indicating that the younger the individual, the greater the tendency toward self-medication (15) (36). Educated individuals seem to believe they have a proper knowledge on drugs, and thus have a greater tendency toward arbitrary drug use which is a false sense of confidence (3). Also, the majority of women who decide not to visit their doctor stated a reason related to illnesses such as cold, headache, minor pain in the back or legs, and stomachache which were regarded as simple diseases not needing a doctor's examination and medication; self-medication in such cases starts with pain killers as well as drugs alleviating the symptoms of cold and fever.…”
Section: Perceived Personal Stonewallingmentioning
confidence: 72%
“…Various studies show a high consumption level of pain killers, vitamins, antibiotics, and Medicinal plants (15,27). In the study conducted by Davati et al (2006), the majority of used drugs included painkillers, digestive drugs, cold drugs, and sleeping pills (3).…”
Section: Perceived Personal Stonewallingmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of traditional Chinese medicine (TCM) is becoming popular around the world (Ge et al, 2014). TCM not only includes herbal plants, but also includes the herbal medicine preparation and formulas well known as Chinese patent medicine (CPM).…”
Section: Introductionmentioning
confidence: 99%